Study of Pavement Performance of Thin-Coat Waterborne Epoxy Emulsified Asphalt Mixture - Cai, Xu; Huang, Wenke; Liang, Juan; Wu, Kuanghuai (Frontiers in Materials, 2020)
Waterborne epoxy emulsified asphalts (WEEA) have high densities, good chemical stabilities, and high viscosities. However, they have problems in terms of overly high stiffness and low-temperature brittleness when applied as thin-coat asphalt mixtures. In this study, testing was conducted to obtain the optimal mixing ratio for WEEA. Anti-sliding, rutting, water stability, Cantabro, and low-temperature bending tests were carried out to evaluate the performance of thin coating layers formed from open graded friction course (OGFC)-5 WEEA mixtures, with the results indicating that the optimal ratio of waterborne epoxy resin emulsion and curing agent was 2:1 and that the dosage of waterborne epoxy resin should be maintained between 15 and 30%. The surface texture depth and British Pendulum Number (BPN) of the OGFC-5 WEEA mixtures were larger than 0.91 mm and 77.4, respectively, and the WEEA mixtures had better water stabilities and spalling resistance performance than a mixture without WEEA. Waterborne epoxy resin dosages of 15 and 30% resulted in WEEA mixture stabilities of up to 4,285 and 8,798 times/mm, respectively, and tensile strengths at -10 ℃ of 2.204 and 4.727 MPa, respectively. The relatively good pavement functional and low-temperature performance of the optimized OGFC-5 WEEA mixture suggest its usefulness as a pavement maintenance material.